Tabebuia serratifolia, Yellow Trumpet Tree - Michael G. Andreu; Melissa H. Friedman; Robert J. Northrop (EDIS)
This deciduous tree is native to South and Central America and is commonly planted in Florida as an ornamental landscape and shade tree. It has attractive, bright yellow blossoms produced in the absence of leaves. Once established, this tree is drought tolerant, making it easier to care for and less demanding on water resources. Yellow trumpet tree also has a relatively high tolerance to salt spray, and therefore is an appropriate street tree or yard specimen in coastal areas. This 2-page fact sheet was written by Michael G. Andreu, Melissa H. Friedman, and Robert J. Northrop, and published by the UF Department of School of Forest Resources and Conservation, July 2012.